2008
DOI: 10.1111/j.1574-6941.2008.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological role of volatiles produced by Epichloë: differences in antifungal toxicity

Abstract: Species of Epichloë (Ascomycota, Clavicipitaceae) are endophytic symbionts of pooid grasses. Sexual reproduction of the fungus depends on gamete-transferring Botanophila flies, which in earlier studies were shown to be specifically attracted by the fungal volatiles chokol K and methyl (Z)-3-methyldodec-2-enoate. As several Epichloë volatiles are known to have antimicrobial properties, it was hypothesised that the original function of insect-attracting volatiles is microbial deterrence. However, the origin of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Functional studies have shown that floral scent mediates a number of different interactions, as it attracts/repels (specific) pollinators, granivores, and herbivores (Baldwin et al 1997;Dötterl et al 2006;Huber et al 2005;Kessler et al 2008;Ô mura et al 2000;Plepys et al 2002) and is thus an important factor for outcrossing (Kessler et al 2008), species isolation (Waelti et al 2008), and damage to seeds and vegetative parts of the plant (Baldwin et al 1997). Floral scent compounds can also act as a powerful anti-microbial agent (Steinebrunner et al 2008). Despite this wealth of functions and the clear importance of scent in the ecology of plants, studies on phenotypic selection on individual floral scent compounds have not yet been done.…”
Section: Introductionmentioning
confidence: 98%
“…Functional studies have shown that floral scent mediates a number of different interactions, as it attracts/repels (specific) pollinators, granivores, and herbivores (Baldwin et al 1997;Dötterl et al 2006;Huber et al 2005;Kessler et al 2008;Ô mura et al 2000;Plepys et al 2002) and is thus an important factor for outcrossing (Kessler et al 2008), species isolation (Waelti et al 2008), and damage to seeds and vegetative parts of the plant (Baldwin et al 1997). Floral scent compounds can also act as a powerful anti-microbial agent (Steinebrunner et al 2008). Despite this wealth of functions and the clear importance of scent in the ecology of plants, studies on phenotypic selection on individual floral scent compounds have not yet been done.…”
Section: Introductionmentioning
confidence: 98%
“…These two compounds are thought to be specific to Epichloë, and Steinebrunner et al (2008aSteinebrunner et al ( , 2008bSteinebrunner et al ( , 2008c have hypothesized that chokol K is an antimicrobial compound that has evolved secondarily as a pollinator attractant. More parallels between flowering plants and fungi can be made when considering the sexual reproduction of stinkhorns, a group of fungi that are renowned for the shape of their fruiting bodies, which are similar in shape to an erect penis.…”
Section: Trends In Floral Scentsmentioning
confidence: 98%
“…Syndromes (or adaptive peaks in the olfactory landscape) of saprophily High amounts of p-cresol, low amounts of polysulfides Mimicry of herbivore dung Low amounts of p-cresol, high amounts of (dimethyl) oligosulfides Mimicry of carnivore or omnivore carrion or dung High amounts of heptanal and octanal Mimicry of carnivore or omnivore carrion or dung High amounts of hexanoic acid Mimicry of urine gnats as pollinators of flowering plants seems quite limited (Vogel 1978;Okuyama et al 2004Okuyama et al , 2008 and references therein; Goldblatt et al 2004;Blanco and Barboza 2005 (Schardl 1996), are attracted primarily by two uncommon odour compounds, namely the sesquiterpene alcohol (chokol K) and methyl (Z)-3-methyldodec-2-enoate Steinebrunner et al 2008aSteinebrunner et al , 2008bSteinebrunner et al , 2008c. These two compounds are thought to be specific to Epichloë, and Steinebrunner et al (2008aSteinebrunner et al ( , 2008bSteinebrunner et al ( , 2008c have hypothesized that chokol K is an antimicrobial compound that has evolved secondarily as a pollinator attractant.…”
Section: Trends In Floral Scentsmentioning
confidence: 99%
“…Thus, chokol B (6) [16,18], chokol C (7) [15,16,18], chokol D (8) [15,16,18], chokol E (9) [16], chokol H (10) [15], chokol I (11) [15], chokol J (12) [15], chokol K (13) [15], chokol L (14) [15] and chokolal A (15) [15] possess the complete C-15 sesquiterpene carbon framework. Chokol A (16) [15,16,18], chokol F (17) [15,16], chokolic acid A (18) [15] and chokolic acid B (19) [15] and their derivatives (21)(22)(23)(24) [15] lost three carbons of their side chain. Finally, chokol G (20) [15,16] was the only natural compound possessing 11 carbon atoms.…”
Section: Occurrence-bioactivitymentioning
confidence: 99%
“…Chokol K (13) produced by Epicloë typhina when infecting Anthoxanthum odoratum attracted female flies acting as gamete transferors from one mating type to the opposite mating type [19], whilst fly larvae feed and develop on the fertilized fungal fruiting structures [20]. In this sense, it has been recently reported that chokol K, when added (200 mg) to agar Petri dishes significantly reduced the spore germination of all plant pathogenic fungi tested, namely, Clonostachys sp., Nodulisporium sp., Stagonospora nodorum, Mycosphaerella graminicola, Epicloë clarkii and Epicloë bromicola, suggesting that fungal volatile substances have followed an evolutionary pathway from defence to attraction [21].…”
Section: Occurrence-bioactivitymentioning
confidence: 99%